2019
DOI: 10.1002/er.4456
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of an integrated concentrated solar and wind energy system with storage

Abstract: Summary This study analyzes a renewable energy‐driven innovative multigeneration system, in which wind and solar energy sources are utilized in an efficient way to generate several useful commodities such as hydrogen, oxygen, desalted water, space cooling, and space heating along with electricity. A 1‐km2 heliostat field is considered to concentrate the solar light onto a spectrum splitter, where the light spectrum is separated into two portions as reflected and transmitted to be used as the energy source in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The range of flashing temperature can be found from Equation (12)ΔF=(Tb1TbN)NN1where Tb1 and TbN are brine temperatures in the first and last stages, respectively. The PR is the amount of distillate produced from the condensation of 1 kg of steam at an average temperature corresponding to the 2330 kJ kg −1 latent heat and can be expressed as follows [ 23 ] PR=mfalse.distillateQfalse.desalination2330where trueQ.desalination is the heat supplied to the desalination unit. The gain ratio (GR) is found usingGR=LHS2330PRwhere LHS is the latent heat of steam at atmospheric pressure.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of flashing temperature can be found from Equation (12)ΔF=(Tb1TbN)NN1where Tb1 and TbN are brine temperatures in the first and last stages, respectively. The PR is the amount of distillate produced from the condensation of 1 kg of steam at an average temperature corresponding to the 2330 kJ kg −1 latent heat and can be expressed as follows [ 23 ] PR=mfalse.distillateQfalse.desalination2330where trueQ.desalination is the heat supplied to the desalination unit. The gain ratio (GR) is found usingGR=LHS2330PRwhere LHS is the latent heat of steam at atmospheric pressure.…”
Section: System Descriptionmentioning
confidence: 99%
“…Ozlu and Dincer [ 22 ] thermodynamically analyzed an integrated system powered by solar energy and found that it was capable to produce 0.04 kg s −1 of distilled water. Sezer et al [ 23 ] suggested an integrated system that utilizes solar and wind energies to provide heating and cooling, electricity, hydrogen, and freshwater. The gain ratio and PR of the desalinated unit were computed as 14.36 and 14.82, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies tackled the design and analysis of novel multigeneration systems utilizing different renewable energy sources. Some proposed designs operate with solar energy‐based systems, 4-6 wind and solar hybrid systems, 7,8 solar‐ocean hybrid system, 9 solar and hydrogen‐based systems, 10 solar and geothermal‐based systems, 11-13 biomass‐based systems, 14,15 etc.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is unaffected by the current mismatch and is helpful to reduce the use of stringent tracking and cooling techniques because it is operated at low optical concentrations . The spectrum splitting approach can also be utilized in several hybrid systems to make full use of the incident solar spectrum, such as multijunction solar cell systems, photovoltaic (PV)/thermal spectrum splitting systems, photovoltaic/hydrogen spectrum splitting systems, and energy storage . Study on the spectrum splitting systems has been conducted early.…”
Section: Introductionmentioning
confidence: 99%